ANALISIS BIAYA DAN PENGUKURAN KUALITAS HIDUP YANG DIUKUR MENGUNAKAN INSTRUMEN EQ-5D PADA PASIEN PENYAKIT GAGAL GINJAL KRONIS YANG MENJALANI PENGOBATAN HEMODIALISIS - Yumassik, Abdul Mahmud; Aisyah, Noor; Putri, Devita Eliana (Jurnal Insan Farmasi Indonesia, 2023)
Treatment of end-stage chronic kidney failure is usually carried out by administering hemodialysis. This action has an impact on social, financial  and psychological                        conditions and reduces the quality of life. The aim of this research is to determine the quality of life of chronic kidney failure patients who undergo hemodialysis and to calculate the average cost of drugs and medical equipment for hemodialysis. The research method was a crosssectional design, the data taken in August-September 2023 at Ulin Hospital Bajarmasin. The consecutive sampling t resulted in 70 respondents. Calculation of quality of life using the EQ-5D index calculator and the average cost using Microsoft Excel. The results showed that the cost of medicine was IDR.9,805,345 and medical equipment costs IDR.12,754.630,  it was calculated for treatment for 1 month. The quality of life of patients who underwent hemodialysis was found to be 65% good and 34.3% poor quality of life where the average value of quality of life had an index of 0.6631. The conclusion obtained is that the cost for 1 month is IDR. 22,559,975 and the quality of life of patients undergoing hemodialysis treatment is in the good category with an average health index value of 0.6631.